Utilizing genomic analyses to investigate the first outbreak ofvanAvancomycin‐resistantEnterococcusin Australia with emergence of daptomycin non‐susceptibility. Issue 3 (March 2019) - Douglas, Abby P.; Marshall, Caroline; Baines, Sarah L.; Ritchie, David; Szer, Jeff; Madigan, Victoria; Chan, Hiu Tat; Ballard, Susan A.; Howden, Benjamin P.; Buising, Kirsty; Slavin, Monica A.
Abstract : Introduction. : The majority of vancomycin‐resistant Enterococcus faecium (VREfm) in Australia is of the vanB genotype. An outbreak of vanA VREfm emerged in our haematology/oncology unit between November 2014 and May 2015. The first case of daptomycin non‐susceptible E. faecium (DNSEfm) detected was a patient with vanA VREfm bacteraemia who showed clinical failure of daptomycin therapy, prompting microbiologic testing confirming daptomycin non‐susceptibility. Objectives. : To describe the patient profiles, antibiotic susceptibility and genetic relatedness of vanA VREfm isolates in the outbreak. Methods. : Chart review of vanA VREfm colonized and infected patients was undertaken to describe the demographics, clinical features and outcomes of therapy. Whole genome sequencing of vanA VREfm isolates involved in the outbreak was conducted to assess clonality. Results. : In total, 29 samples from 24 patients tested positive for vanA VREfm (21 screening swabs and 8 clinical isolates). Five isolates were DNSEfm (four patients colonized, one patient with bacteraemia), with only one patient exposed to daptomycin previously. In silico multi‐locus sequence typing of the isolates identified 25/26 as ST203, and 1/26 as ST796. Comparative genomic analysis revealed limited core genome diversity amongst the ST203 isolates, consistent with an outbreak of a single clone of vanA VREfm. Conclusions. : Here we describe an outbreak of vanA VREfm in a haematology/oncology unit. Genomic analysis supports transmission of an ST203 vanA VRE clone within this unit. Daptomycin non‐susceptibility in 5/24 patients left linezolid as the only treatment option. Daptomycin susceptibility cannot be assumed in vanA VREfm isolates and confirmatory testing is recommended.